2023
DOI: 10.1097/dbp.0000000000001141
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Suicide Risk in Primary Care: Cost Savings Associated with Diverting Patients From Emergency Departments

Abstract: There is emerging evidence that integrated medicalbehavioral health care reduces reliance on the emergency department (ED) for managing mental health crises. 16 This study builds on this body of literature by demonstrating the exact magnitude of the financial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…These findings counter common concerns from providers and families that suicide screening may be iatrogenic or lead to marked increases in ED utilization (32)(33)(34). This study replicated a previous finding that over 90% of screen-positive youth who received a same-day IBH consult were diverted from the ED on both the day of their positive screen and during the subsequent month (7). However, we found that youth with positive screens who did not receive sameday IBH were also diverted from the ED at high rates.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These findings counter common concerns from providers and families that suicide screening may be iatrogenic or lead to marked increases in ED utilization (32)(33)(34). This study replicated a previous finding that over 90% of screen-positive youth who received a same-day IBH consult were diverted from the ED on both the day of their positive screen and during the subsequent month (7). However, we found that youth with positive screens who did not receive sameday IBH were also diverted from the ED at high rates.…”
Section: Discussionsupporting
confidence: 88%
“…These results should be interpreted in the context of the broader roll-out of ASQ screening and systematic risk determination in the clinics under study. In contrast to Mancini and colleagues (7), who compared rates of IBH-associated ED diversion to a pre-IBH norm of referring all youth with positive screens to the ED, medical providers in our study did not refer all positive screens to the ED as a matter of course. Consistent with the U.S. National Strategy for Suicide Prevention (35), medical personnel in our clinic were trained in a secondary assessment process as part of implementing the ASQ.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations